Consumer familiarity, perspectives and expected value of personalized medicine with a focus on applications in oncology. (January 2015) - Garfield, Susan; Douglas, Michael P; MacDonald, Karen V; Marshall, Deborah A; Phillips, Kathryn A
Aims: Knowledge of consumer perspectives of personalized medicine (PM) is limited. Our study assessed consumer perspectives of PM, with a focus on oncology care, to inform industry, clinician and payer stakeholders' programs and policy.Materials & Methods: A nationally representative survey of 602 US consumers' ≥30 years old explored familiarity, perspectives and expected value of PM.Results: Most (73%) respondents have not heard of 'personalized medicine, ' though after understanding the term most (95%) expect PM to have a positive benefit. Consumer's willingness to pay is associated with products' impact on survival, rather than predicting disease risk. If testing indicates consumers are not candidates for oncology therapies, most (84%) would seek a second opinion or want therapy anyway.Conclusions: Understanding heterogeneity in consumer perspectives of PM can inform program and policy development.